2019
DOI: 10.1016/j.disc.2019.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Antimagic orientations of disconnected even regular graphs

Abstract: A labeling of a digraph D with m arcs is a bijection from the set of arcs of D to {1, 2, . . . , m}. A labeling of D is antimagic if no two vertices in D have the same vertexsum, where the vertex-sum of a vertex u ∈ V (D) for a labeling is the sum of labels of all arcs entering u minus the sum of labels of all arcs leaving u. An antimagic orientation D of a graph G is antimagic if D has an antimagic labeling. Hefetz, Mütze and Schwartz in [J. Graph Theory 64(2010)219-232] raised the question: Does every graph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…Particularly, they showed that every orientation of stars (other than K1,2), wheels, and complete graphs (other than K3) is antimagic. Conjecture 1 has been also verified for regular graphs [9,13,15,17], biregular bipartite graphs with minimum degree at least two [14], Halin graphs [20], graphs with large maximum degree [18], and graphs with large independence number [16]. In this paper, by supporting Conjecture 1 we obtain the results below.…”
Section: Introductionsupporting
confidence: 74%
“…Particularly, they showed that every orientation of stars (other than K1,2), wheels, and complete graphs (other than K3) is antimagic. Conjecture 1 has been also verified for regular graphs [9,13,15,17], biregular bipartite graphs with minimum degree at least two [14], Halin graphs [20], graphs with large maximum degree [18], and graphs with large independence number [16]. In this paper, by supporting Conjecture 1 we obtain the results below.…”
Section: Introductionsupporting
confidence: 74%
“…Particulary, they showed that every orientation of stars (other than K 1,2 ), wheels, and complete graphs (other than K 3 ) is antimagic. Conjecture 2 has been also verified for regular graphs [9,12,14,16], biregular bipartite graphs with minimum degree at least two [13], Halin graphs [19], graphs with large maximum degree [17], and graphs with large independence number [15]. In this paper, by supporting Conjecture 2, we obtain the results below.…”
Section: Introductionsupporting
confidence: 73%
“…In [7], Hefetz, Mütze and Schwartz proved Conjecture 1 for some classes of graphs, such as stars, wheels, and graphs of order n with minimum degree at least c log n for an absolute constant c. In the process the authors proved a stronger result that every orientation of these graphs is antimagic as well. Additional cases for this conjecture that have been proved already include regular graphs [7,9,16,15], biregular bipartite graphs with minimum degree at least two [13], Halin graphs [18], graphs with large maximum degree [17], graphs with minimum degree at least 33 and bipartite graphs with no vertex of degree 0 or 2 [12]. Researchers have taken particular interest in investigating trees, as we do.…”
Section: Introductionmentioning
confidence: 72%